Research methodology : concepts and cases - Chawla, Deepak; Sondhi, Neena (Vikas Publishing, 2011)
Research methodology, concepts and cases provides a comprehensive and stepwise understanding of the research process with a balanced blend of theory, techniques and Indian illustrations from a wide cross-section of business areas. This book makes no presumptions and can be used with confidence and conviction by both students and experienced managers who need to make business sense of the data and information that is culled out through research groups. The conceptual base has been provided in comprehensive, yet simplistic detail, addressing even the minutest explanations required by the reader. The language maintains a careful balance between technical know-how and business jargon. Every chapter is profusely illustrated with business problems related to all domains - marketing, finance, human resource and operations. Thus, no matter what the interest area may be, the universal and adaptable nature of the research process is concisely demonstrated -- Publisher's website